Formulation, evaluation and optimization of sustained release matrix tablets of captopril - V Pinank Pandya; B Vandana Patel; Prajesh Patel (Wolters Kluwer Medknow Publications, 2012)
Sustained release matrix tablet is a delivery system by which the drug can be delivered at a controlled rate for long period of time. The present study aims at formulation, evaluation and optimization of captopril matrix tablets. A 3 2 full factorial design was adopted and all 9 batches were prepared by wet granulation method. Prepared granules and tablets were evaluated for precompression and postcompression characteristics respectively. Check point analysis was applied to the observations and the formula of the tablet was optimized. Optimized formula, F6 showed zero order drug release kinetics for the time period of 24 hours i.e. 17.55% release at the end of 2 hours, 53.4% release at the end of 12 hours and 100.24% release at the end of 24 hours. The results revealed that concentration of matrix forming agent and solution of granulating agent significantly affected in vitro drug release profile.